Mixed Controller Design for an Uav Flight Control System - Alvarez-Guenchuman, J; Acosta-Barbosa, K (Institute of Electrical and Electronics Engineers Inc., 2016)
This paper presents the design of a robust mixed controller for the Delta wing UAV control system. The proposed controller combines H∞ and PID control techniques to achieve the criteria of performance and robustness required by the system against to disturbances caused by the wind. Used as inner loop, the H∞ controller regulates system variables, while references correction is performed in an outer loop by a PID controller. Computational simulations are performed in order to show the advantages of the proposed controller, particularly an improved response in the time domain for the UAV system variables. © 2015 IEEE.